2017
DOI: 10.1002/iid3.154
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3supplementation of a high fat high sugar diet ameliorates prediabetic phenotype in female LDLR−/−and LDLR+/+mice

Abstract: IntroductionFatty liver disease is prevalent in populations with high caloric intake. Nutritherapeutic approaches are being considered, such as supplementary Vitamin D3, to improve aspects of metabolic syndrome, namely fatty liver disease, hyperlipidemia, and insulin resistance associated with obesity.MethodsWe analyzed female LDLR−/− and LDLR+/+ mice on a 10‐week diabetogenic diet for markers of fatty liver disease, metabolic strain, and inflammation.ResultsThe groups on a high fat high sugar diet with supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Similar results were recently reported by Jin et al (49) using intraperitoneal VD administration in MSG-obese rats. VD supplementation also improved the metabolic profile in HFD-obese mice and in LDL receptor knockout mice (8) . The association between VD and lipid profiles, including TAG, was demonstrated in a longitudinal study by Jorde et al (55) .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Similar results were recently reported by Jin et al (49) using intraperitoneal VD administration in MSG-obese rats. VD supplementation also improved the metabolic profile in HFD-obese mice and in LDL receptor knockout mice (8) . The association between VD and lipid profiles, including TAG, was demonstrated in a longitudinal study by Jorde et al (55) .…”
Section: Discussionmentioning
confidence: 88%
“…Thus, obesity and the metabolic syndrome are conditions intimately related to the development of type 2 diabetes mellitus and CVD worldwide (7,(9)(10)(11) . It has been demonstrated that VD supplementation could improve glucose tolerance, pancreatic β-cell function and insulin sensitivity (6)(7)(8)12,13) , although these actions have not been confirmed by all authors (14)(15)(16)(17) . VD has direct effects on the endocrine pancreas (12) .…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…VD mediates anti-inflammatory effects and has been shown to reduce HFD-induced increases in tumor necrosis factor α (TNFα) and pro-inflammatory cytokines such as interleukin (IL) -6 and lipid peroxidation products [ 60 , 61 ]. Besides anti-inflammatory effects VD has also been shown to have anti-oxidative effects by expression of anti-oxidative enzymes such as superoxide dismutase (SOD), glutathione (GSH), and catalase [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%